The applications of Ursodeoxycholic acid in infant with cholestasis: A retrospective cohort analysis - Hanifah, Nur; Setyoboedi, Bagus; Wungu, Citrawati Dyah Kencono; Prihaningtyas, Rendi Aji (Edelweiss Applied Science and Technology, 2024)
Biliary atresia is the predominant etiology of cholestasis in early infancy. Impairment of bile fluid excretion results in elevated bilirubin levels, causing a yellowing of the skin. Ursodeoxycholic acid is well-established to enhance liver function when taken promptly. The application of ursodeoxycholic acid for treating cholestasis in pediatric patients remains contentious. The objective of this study is to assess the impact of ursodeoxycholic acid treatment on liver biomarkers in infant with cholestasis. This was retrospective cohort study in infant with cholestasis who underwent ursodeoxycholic acid treatment for two weeks. Secondary data including aspartate aminotransferase, alanine aminotransferase, total bilirubin, and direct bilirubin were extracted from the medical records of the outpatient clinic in the Department of Child Health at Dr. Soetomo General Hospital, Indonesia (January 2020 - December 2023). The data was devided into two groups based on biopsy and examined utilizing SPSS version 23. This study included 64 participants. Statistics show an equal gender ratio. Ursodeoxycholic acid treatment in paediatric cholestasis patients can lower liver biomarker level. Levels of total bilirubin and direct bilirubin diminished in individuals both groups. Notable levels were recorded in individuals with normal biopsy outcomes (p=0.007 and p=0.012). Administration of ursodeoxycholic acid markedly elevated ALT levels in both the normal and abnormal liver biopsy outcome groups (p=0.031 and p=0.006). Ursodeoxycholic acid has been shown to be effective in improving liver function in infant with cholestasis. In order to avoid negative effects, the medication must be carefully administered to people who already have liver fibrosis.